2009
DOI: 10.2353/ajpath.2009.090328
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferon Modulates Monocyte Recruitment and Maturation in Chronic Inflammation

Abstract: Chronic inflammation is characterized by continuous recruitment and activation of immune cells such as monocytes in response to a persistent stimulus. Production of proinflammatory mediators by monocytes leads to tissue damage and perpetuates the inflammatory response. However, the mechanism(s) responsible for the sustained influx of monocytes in chronic inflammation are not well defined. In chronic peritonitis induced by pristane, the persistent recruitment of Ly6C hi inflammatory monocytes into the peritoneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
172
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(195 citation statements)
references
References 55 publications
19
172
1
3
Order By: Relevance
“…Furthermore, IFN-induced 25-HC was shown to broadly suppress IL-1-activating inflammasomes (63), in line with the known immunosuppressive activity of type I IFNs (3). Consistent with a role in dampening inflammation, we also found that ATF3 regulates the expression of the IFN-inducible chemokines CCL3 and CCL12, which are required for inflammatory monocyte recruitment (64). The overrepresentation of cell surface markers/receptors and chemokines (Supplemental Table II) in addition to Ch25h suggests that ATF3 might be induced by IFN to limit subsequent inflammation and modulate the adaptive immune response.…”
Section: Isgs Similar To Atf3supporting
confidence: 54%
“…Furthermore, IFN-induced 25-HC was shown to broadly suppress IL-1-activating inflammasomes (63), in line with the known immunosuppressive activity of type I IFNs (3). Consistent with a role in dampening inflammation, we also found that ATF3 regulates the expression of the IFN-inducible chemokines CCL3 and CCL12, which are required for inflammatory monocyte recruitment (64). The overrepresentation of cell surface markers/receptors and chemokines (Supplemental Table II) in addition to Ch25h suggests that ATF3 might be induced by IFN to limit subsequent inflammation and modulate the adaptive immune response.…”
Section: Isgs Similar To Atf3supporting
confidence: 54%
“…It is known that local type I IFNs are secreted rapidly following HSV-2 infection (19). In addition, type I IFNs have been shown to induce CCR2 ligand expression and recruitment of monocytes (20). Notably, CCR2 ligand production was almost undetectable in the genital mucosa of HSV-2-infected IFN-αβR −/− mice (Fig.…”
Section: Inflammatory Monocytes Require Ccr2 For Entry Into Hsv-2-infmentioning
confidence: 92%
“…It is induced by donor T cells and inflammatory cytokines causing damage to host epithelial tissues, predominantly the skin, liver and gastrointestinal tract. [1][2][3] Despite pharmacological prophylaxis, about half of the patients receiving allogeneic hematopoietic stem cell transplantation experience severe aGVHD, which requires high-dose steroid treatment and often has a highly unsatisfactory outcome. Therefore, an immunomodulatory regimen is urgently needed for aGVHD prevention and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] S1P is mainly produced by erythrocytes and endothelial cells. S1P binds to five known G protein-coupled receptors, S1P [1][2][3][4][5] , and acts as a second messenger during cell signaling. 8,9 Most S1P-dependent immune modulations were discovered using the receptor agonist FTY720.…”
Section: Introductionmentioning
confidence: 99%